The Impact of Selenium and Levothyroxine on the Immune System of Hypothyroid Rats - Sabea, Aryaf M.; Al-Qaiym, Majida A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The immune system and thyroid hormones have an inverse relationship, but both thyroid hormones and selenium play a crucial role in the immune system. However, when the levels of thyroid hormones decrease (known as hypothyroidism), their effect on immune system cells and their relationship with selenium supplements in the body are not well understood.Objectives: The aim of this study was to investigate the impact of Se-nanoparticles on thyroid hormones and the blastogenic response of lymphocytes in various lymphoid tissues in rats with hypothyroidism.Methods: A group of female Wister rats aged three to four months were randomly placed into five groups (each group has 6 rats) and were given  a basal diet on a daily basis. However, the daily water supply given to each group was different. The first group was the control group and received normal water, while the other four groups were given 0.02% methimazole in their drinking water every day for four weeks to induce hypothyroidism. Once the hypothyroidism was confirmed, the 3rd, 4th, and 5th experimental groups were given one of the following three treatments for four weeks, respectively: SC-SeNPs (0.1mg selenium per kg per day) as T1, Levothyroxine (0.9μg per 100g per day) as T2, or SC-SeNPs (0.1 mg selenium per kg per day) and Levothyroxine (0.9μg per 100g per day) as T3. In the end, blood samples were collected from euthanized animals using a high dose of anesthesia, and lymphoid tissue samples (spleen, Peyer’s patches and mesenteric lymph node) were preserved in 10% formalin.Results: Our research has revealed that IgG, a humoral immunity marker, was found to be significantly decreased in hypothyroidism. However, when treated with  levothyroxine alone or in combination with Sc-SeNPs, the level of cellular immunity marker, IL-6, was found to be significantly increased in hypothyroidism when compared to the control group. Additionally, we observed histopathological changes in the lymphoid tissue of hypothyroidism rats, which included depletion of the white pulp of spleen with congestion in the blood vessels, a decrease in the lymphoid follicle of Peyer’s patches, and  a decrease in  the primary  and secondary follicles of the mesenteric lymph nodes .Conclusion:  Thyroid hormones play a role in regulating innate and adaptive immunity. The combination of selenium with levothyroxine is  the most effective treatment for  hypothyroidism and improving the activity of the immune system cells .